Answer:
3 + 9i
Step-by-step explanation:
(4 + 2i) - (1 - 7i)
distribute the (-)
(4 + 2i) - 1 + 7i
combine like terms
3 + 9i
Answer:
- f(x) = 2x -2/3
- f(3) = 5 1/3
Step-by-step explanation:
We solve an equation for a specific variable by using inverse operations to undo what is done to the variable. The resulting function is evaluated by substituting the given value for the variable.
__
<h3>a.</h3>
We are given the equation ...
6x -3y = 2
Solving for y, we get ...
6x -2 = 3y . . . . . add 3y-2 to both sides
2x -2/3 = y . . . . . divide by 3
f(x) = 2x -2/3 . . . . write using functional notation
__
<h3>b.</h3>
To find f(3), we use x=3 in the function.
f(3) = 2(3) -2/3 = 6 -2/3
f(3) = 5 1/3
The absolute value equation with the wanted solutions is:
|x| - 1/2 = 0
<h3>
How to find the absolute value equation?</h3>
Here we want to find an absolute value equation such that the solutions are:
x = -1/2 and x = 1/2.
Remember that the absolute value equation always changes the sign, such that the outcome is positive.
This means that:
|1/2| = 1/2
|-1/2| = 1/2
Then a trivial equation with these two solutions is:
|x| - 1/2 = 0
Where the two solutions are x = 1/2 and x = -1/2.
If you want to learn more about absolute value equations:
brainly.com/question/5012769
#SPJ1
Answer:
A=πr2 is the formula of pi so
it would be A=3.14*100
or 3.14*10^2
3.142 is not pi
and 20 is not 10^2
Step-by-step explanation: